Editorial (2022)
The Sociedad Colombiana de Ciencas Hortícolas - SCCH (Colombian Society of Horticultural Sciences) and Universidad Pedagógica y Tecnológica de Colombia - UPTC as institutions responsible for publication of the Revista Colombiana de Ciencias Hortícolas (Colombian Journal of Horticultural Sciences) extend their greetings to our scientific community overwhelmed by the consequences of the COVID-19 pandemic, which affected availability of economic resources, imposed difficulties for mobility of researchers, and contributed significantly to reducing research and scientific productivity. We also want to greet our authors and readers, who during their new mode of work and despite the many difficulties, continue to generate and disseminate the knowledge in area of horticulture and other species, thus, contributing to strengthen new schemes within the global food system and to develop studies with other important plant species in world trade.